Absential Suspension: Malebranche and Locke on Human Freedom - Julie Walsh (Journal of Modern Philosophy)
This paper treats a heretofore-unnoticed concept in the history of the philosophical discussion of human freedom, a kind of freedom that is not defined solely in terms of the causal power of the agent. Instead, the exercise of freedom essentially involves the non-occurrence of something.That being free involves the non-occurrence, that is, the absence, of an act may seem counterintuitive. With the exception of those specifically treated in this paper, philosophers tend to think of freedom as intimately involved with volition, the judging or deciding activity of the will that votes in favor of or against a proposed action. However, there are two thinkers who endorse a view where not willing constitutes human freedom. Our analysis focuses on the views of Malebranche and Locke. Both invoke a notion dubbed here as ‘absential suspension.’ On this view, freedom is associated not with the power of volition, but rather with this kind of suspension.